IMPLEMENTASI KONTROLER PID DENGAN METODE TUNING ZIEGLER-NICHOLS DAN COHEN-COON PADA SISTEM SCADA KENDALI LEVEL AIR - Hadi Supriyanto; Fitria Suryatini; Abdur Rohman Harits Martawireja; Hendy Rudiansyah (Jurnal Teknologi Terapan, 2022)
Didactics or mini plant teaching aids help students in colleges to understand the use of industrial equipment The SCADA-based water level control system is one of the teaching aid simulator equipment for monitoring and controlling water levels. In this research, PLC is used as a controller with three I/O modules  digital input module, digital output, and analog input and output. Arduino is also used as an analog output converter from PLC to actuator. The control method used is PID control. In the PID control, there are control parameters, namely Kp, Ki, and Kd. The third parameter was determined by the Ziegler-Nichols tuning method and compared with the Coohen-Coon method. The SCADA software that used is Wonderware Intouch on a system using a kepserver. The results of this study indicate that the Cohen-Coon tuning method for proportional control Kp = 1 produces the best response in water level control with a settling time of 21s and a rise time of 18s.